THE EUROPEAN GREEN DEAL: POTENTIALS AND IMPLICATIONS FOR AFRICA - Adewale-Alfred, Prevail Adewale-Alfred (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2024)
This essay will examine the implications of the externalization and globalization of the European Green Deal for Africa. The challenges posed to specific sectors and the potentials for growth and cooperation between the two continents. These possible outcomes are numerous, but we focus on some of the most prevalent and/or serious ones below. We begin by examining broadly the EGD and Africa. Thereafter the Implications and potentials.